Choice architecture and incentives increase COVID-19 vaccine intentions and test demand - Marta Serra-Garcia; Nora Szech (Wissenschaftszentrum Berlin für Sozialforschung (WZB), 2021)
Willingness to vaccinate and test are critical in the COVID-19 pandemic. We study the effects of two measures to increase vaccination and testing: "choice architecture" and monetary compensations. Choice architecture has the goal of "nudging" people into a socially desired direction without affecting their choice options. Compensations reward vaccine takers and are already in use by some organizations. Yet there is the concern that compensations may decrease vaccination if compensations erode intrinsic motivation to vaccinate. We show that both approaches, compensations and choice architecture, significantly increase COVID-19 test and vaccine demand. Yet, for vaccines, low compensations can backfire.
Keywords: D01; D04; I12; 330; choice architecture; incentives; COVID-19; vaccine hesitancy; test avoidance